Study Entamoeba Species in Livestock by Nested Multiplex PCR in Baghdad City - Lina A. Jebur; Athmar K. Abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of the study was to diagnose the Entamoeba spp. in cattle and sheep by using PCR method, foridentified some of these species used the Nested multiplex PCR. The nested multiplex polymerase chainreaction was conducted using the small subunit 18S rRNA gene , the results show total infection rate ofEntamoeba spp was (60%) which include to(30%) in cattle and 30%in sheep. The results second reactionshow that the percent of E.histolytica was (30%) in cattle and (30%) in sheep